Karakterisasi Fisik dan Aktivitas Antioksidan Masker Wajah Gel Pell Off Yang Mengandung Sari Buah Naga (Hylocerus polyrhizus) - Setiawati, Ririn; Sukmawati, Anita (Universitas Muhammadiyah Surakarta, 2018)
Damaged skin due to free radicals from ultraviolet radiation can be prevented using antioxidants. Red dragon fruit (Hylocereus polyrhizus) containing antioxidants can be made into a peel off gel face mask using gelatin as a gelling agent to be applied easily to the skin. The purpose of this study is to determine the effect of various gelatin concentrations on the physical properties and antioxidant activity of peel off gels containing red dragon fruit juice. The peel off gels face mask were made using various gelatin concentration i.e 7.5% w/w (F1); 10% w/w (F2); and 12.5% w/w and containing 10% w/w red dragon fruit. The peel off gels then evaluated for physical properties and antioxidant activity using DPPH. The result showed that the increasing of the gelatin concentration would increase the drying time and adhesive ability of the peel off gels. The escalation of gelatin concentration from 7.5% w/w (F1) to 10% w/w (F2) did not affect the spreading ability of the peel off gel. However, the spreading ability of the peel off gel decreased with the increasing concentration of gelatin from 10% w/w (F2) to 12.5% w/w (F3). The antioxidant test of peel off gel had an average percentage of inhibition of 9.101% (F1); 12.469% (F2); and 15.109% (F3). Based on the results of physical properties and antioxidant activity showed that formula 2 was recomended.